Comparison Between Outcome of Patients Following Saline Irrigation Versus Dry Mopping after Laparoscopic Cholecyetectomy - Muhammad Saad Usmani, Aisha Khatoon, Shua Nasir, Naveed Khan, Alvia Saad, Lal Shahbaz (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Laparoscopic cholecystectomy is minimal invasive procedure of choice for diseases due to gall bladder diseases due to reduced morbidity, comfort and patient’s early hospital discharge. Studies showed stone spillage with its retrieval from the fossa of gall bladder can be done by irrigation or be mopping with surgical gauze. Aims: To Compare between outcome of patients following saline irrigation versus dry mopping after laparoscopic cholecystectomy. Methodology: This was a cross-sectional study conducted at Hanif hospital from July 2019- May 2022 after taking ethical committee review. The study was conducted on 214 patients. The inclusion criteria involved age>18yrs till 60years either gender, with symptomatic gallstones. The patients with choledocholithiasis, immunocompromised, bleeding disorders were excluded. Results: Out of 214 patients enrolled in study mean age of patients was 42.63 ±5.7yrs . There was n=140:74 (65.4%: 34.6%) females: males. In 86% patients with laparoscopic cholecystectomy there was no complication of biliary spillage, while 14% patients experienced spillage of stones intraoperatively. All patients with dry mopping showed less postoperative pain and were discharged early from the hospital. However, the patients with wet irrigation had postoperative moderate pain. Surgical site infection was reported in 5 patients out of 15 patients with wet irrigation compared to dry mopping n=1 with prolonged hospital stay in patients with wet irrigation die to pain and surgical site infection. There was a statistical significant correlation when compared two groups with respect to hospital stay, postoperative pain, surgical site infection. P value-0.000. Conclusion: Our study has shown dry mopping to be better than wet irrigation in terms of increased postoperative pain, prolonged hospital stay & statistical significant correlation in patients with spillage of stones intraoperatively. Keywords: Stones spillage, dry mopping, wet irrigation